The Effectiveness Of Giving Lemon Aromatherapy To Reduce Nausea And Vomiting In Trimester I Pregnant Women In Mariana Clinic - Ronni Naudur Siregar; Agnes Purba; Sharfina Haslin (TOUR HEALTH JOURNAL, 2022)
Background: Pregnancy for women is a meaningful experience. During pregnancy, women experience physical, hormonal and physiological changes. These changes include body shape, daily habits, cravings or pica, fatigue, nausea, vomiting, and discomfort that arise due to pregnancy, Purpose: This study aims to determine the effectiveness of lemon oil aromatherapy in reducing nausea and vomiting of pregnant women in the first trimester. This type of research is an analytical study with a quasi-experimental design. This research was conducted at Mariana Clinic, Bah Jambi Village, Simalungun Regency. The study population was all pregnant women in the first trimester with a gestational age of 4-16 weeks, with a total sample of 26 people. Method: Data collection was carried out by giving the PUQE instrument before and after being given lemon oil aromatherapy to pregnant women. Then proceed with the data analysis stage using the Wilcoxon test. Results: The study showed that the degree of nausea and vomiting in pregnant women in the first trimester before being given lemon oil aromatherapy was mostly heavy as many as 14 people (53.8%), and after being given lemon oil aromatherapy the majority was mild as many as 17 people (65.4%). There was a difference in the degree of nausea and vomiting before and after being given lemon oil aromatherapy with a p value = 0.000. Discussion and Conclusion: Thus, pregnant women should do lemon oil aromatherapy, because giving lemon oil aromatherapy can reduce the intensity of nausea and vomiting in first trimester pregnant women so they don't become dehydrated